2014
DOI: 10.1002/sm2.34
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Salivary Testosterone Levels, Androgen-Related Genetic Polymorphisms, and Self-Estimated Ejaculation Latency Time

Abstract: IntroductionRecently, testosterone (T) has been shown to be associated with premature ejaculation (PE) symptoms in the literature. Furthermore, studies suggest that the etiology of PE is partly under genetic control.AimThe aim of this study was to reassess findings suggesting an association between testosterone (T) and a key symptom of PE, ejaculation latency time (ELT), as well as exploratively investigating associations between six androgen-related genetic polymorphisms and ELT.Materials and MethodsStatistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…In contrast to the above-mentioned studies that indicate the relationship between the T and PE, Jern et al (2014) did not find any association between the salivary T levels and ejaculatory latency times. In another study, Paduch et al (2015) evaluated the efficacy of T replacement in androgen-deficient men with ejaculatory dysfunction, and suggested that T replacement was not associated with significant improvement in ejaculatory dysfunction in these patients.…”
Section: Introductioncontrasting
confidence: 99%
“…In contrast to the above-mentioned studies that indicate the relationship between the T and PE, Jern et al (2014) did not find any association between the salivary T levels and ejaculatory latency times. In another study, Paduch et al (2015) evaluated the efficacy of T replacement in androgen-deficient men with ejaculatory dysfunction, and suggested that T replacement was not associated with significant improvement in ejaculatory dysfunction in these patients.…”
Section: Introductioncontrasting
confidence: 99%
“…Although that study seems promising, future studies need to further illustrate the underlying mechanism of S. montana . Unfortunately, testosterone levels have not been found to be a negative predictor for PE in humans . In fact, studies have shown that patients with PE have been found to have higher testosterone levels than normal controls .…”
Section: Experimental Animal Modelsmentioning
confidence: 99%
“…Unfortunately, testosterone levels have not been found to be a negative predictor for PE in humans. 128,129 In fact, studies have shown that patients with PE have been found to have higher testosterone levels than normal controls. 128,130 Further study of S. montana in animal models is necessary to identify its ability to increase the ejaculatory latency.…”
Section: Satureja Montanamentioning
confidence: 99%
“…In a recent study, Jern et al. [98] investigated androgen‐related genetic polymorphisms in PE etiology, including the well‐studied androgen receptor gene‐linked cytosine‐adenine‐guanine (CAG) repeat, reporting an association between the 5‐α‐reductase type 2 gene‐linked SNP rs2208532 and ELT, but this association was no longer robust after controlling for multiple testing. However, a sex hormone binding globulin gene‐linked SNP (rs1799941) was found after correction for multiple tests to moderate the association between salivary testosterone (T) levels and ELT, so that A:A genotype carriers expressed lower T levels as a function of increasing ELT compared to carriers of other genotypes at this locus.…”
Section: Genetics Of Pementioning
confidence: 99%
“…Possible associations between PE symptoms and a relatively large number of SNPs linked to the OX receptor and AVP receptors 1A and 1B genes were investigated by Jern et al [97], reporting a heterozygote effect for one OX receptor genelinked SNP (rs75775), but leaving open for interpretation which of the two possible alleles at this locus could have an influence on ejaculatory function. In a recent study, Jern et al [98] investigated androgen-related genetic polymorphisms in PE etiology, including the well-studied androgen receptor gene-linked cytosine-adenine-guanine (CAG) repeat, reporting an association between the 5-α-reductase type 2 gene-linked SNP rs2208532 and ELT, but this association was no longer robust after controlling for multiple testing. However, a sex hormone binding globulin gene-linked SNP (rs1799941) was found after correction for multiple tests to moderate the association between salivary testosterone (T) levels and ELT, so that A:A genotype carriers expressed lower T levels as a function of increasing ELT compared to carriers of other genotypes at this locus.…”
Section: Association Studies Focusing On Nonserotonergic Genesmentioning
confidence: 99%